PENGARUH MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PUSAKAJAYA KABUPATEN SUBANG - Harries Madiistriyatno; Toto Suharto Adiwijaya; Witler Slamat Halomoan Silitonga (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
The success of an organization can not be separated from the quality leader, because a quality leader was able to utilize existing resources within the company, have the ability to direct the activities of subordinates that led, in anticipation of any changes that occur suddenly, it can correct any weaknesses No, could bring the organization to the agreed goals within a predetermined time. Especially for government agencies, particularly in the health sector providing motivation to employees should be continued. This meant that attitude, loyalty and commitment to the Pusakajaya district office increases so that every job will be easier to be completed on time and on target The problems in this study is whether the motivation and leadership significant effect on the performance of employees at Pusakajaya district office Subang? and whether the motivation and leadership partially significant effect on the performance of employees at Pusakajaya district office Subang? The sampling technique systematic method of proportionate stratified random sampling. Data analysis techniques multiple linear regression analysis This research resulted in the conclusion that the motivation and leadership together a significant effect on the performance of employees at Pusakajaya district office Subang. These results can be seen from the F count of 30,650 with a significance level of 0.000, which is smaller than α (0.000 0.050). The influence of work motivation and leadership to employees performance of 50.5% while the remaining 49.5% is influenced by other variables outside of this study. Motivation, and leadership is partially significant effect on the performance of employees at Pusakajaya district office Subang. These results can be seen from the t work motivation of 6.272 with a significance level of 0.006 which is smaller than α (0.000 0.050) and the t variable leadership of 5.906 with a significance level of 0.000, which is smaller than α (0.000 0.050).